Pion-to-vacuum vector and axial vector amplitudes and weak decays of pions in a magnetic field - Coppola, Máximo (2019)
We propose a model-independent parametrization for the one-pion-to-vacuum matrix elements of the vector and axial vector hadronic currents in the presence of an external uniform magnetic field. It is shown that, in general, these hadronic matrix elements can be written in terms of several gauge covariant Lorentz structures and form factors. Within this framework we obtain a general expression for the weak decay pi -> l nu_l and discuss the corresponding limits of strong and weak external magnetic fields.